2021
DOI: 10.1142/s0219649222500034
|View full text |Cite
|
Sign up to set email alerts
|

Association of Corporate Governance with Intellectual Capital Performance: A Study of S&P 200 Companies

Abstract: This paper aims to investigate the relationship between intellectual capital efficiency and the attributes of corporate governance in the top 116 companies from 2012 to 2018. The VAIC has been calculated for the sample chosen, which did not include financial companies. The relationship between corporate governance structure and intellectual capital performance was investigated using panel data regression analysis. Results have shown that board size is negatively associated with intellectual capital and its com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…On the contrary, Mwambuli (2018) found a significant negative effect of board size on capital structure decisions after examining board characteristics and their effects on capital structure decisions in developing economies using a balanced panel dataset of 32 non-financial listed firms in the East African region from 2006-to 2015. This finding is supported by Soriya and Kumar (2022) and Ehikioya et al (2021), that investigated countries of India and Nigeria, respectively, and showed a negative relationship between board size and firm leverage.…”
Section: Literature Reviewsupporting
confidence: 62%
“…On the contrary, Mwambuli (2018) found a significant negative effect of board size on capital structure decisions after examining board characteristics and their effects on capital structure decisions in developing economies using a balanced panel dataset of 32 non-financial listed firms in the East African region from 2006-to 2015. This finding is supported by Soriya and Kumar (2022) and Ehikioya et al (2021), that investigated countries of India and Nigeria, respectively, and showed a negative relationship between board size and firm leverage.…”
Section: Literature Reviewsupporting
confidence: 62%
“…Prior studies have also argued that firms with higher liquidity are likely to invest more (new ventures) to enhance the efficiency of their IC resources (Shahveisi et al, 2017). Finally, prior studies have examined the role of IO, suggesting that institutional investors affect firms' strategic decisions and performance (Alshabibi, 2021;Paputungan et al, 2020;Soriya and Kumar, 2022). Table 1 shows further details regarding the defined set of variables of the current study.…”
Section: Female Directors and Icementioning
confidence: 98%
“…In the present study, resource dependence theory and agency theory have been adopted to support the investigation of the phenomenon as they consider a cognizance-based approach toward developing and using firms' internal sources (resource dependence theory) (Hsu et al, 2018) and affect information asymmetry and agency costs (agency theory) related to IC by monitoring the board of directors' structure and roles (Smriti and Das, 2021;Zahra and Pearce, 1989). Resource dependence theory proposes that one of the main factors behind a firm's success is its open system, which is related to the interdependent relationship between external resources and firms (Davis and Adam, 2010;Pfeffer and Salancik, 1978;Scafarto et al, 2020;Soriya and Kumar, 2022). It considers the boardroom as an adviser that supplies resources to the firm through its members' informative skills and experience (Pfeffer and Salancik, 1978).…”
Section: Female Directors and Icementioning
confidence: 99%
See 1 more Smart Citation
“…Second phase started from 2001 to 2010 and was immensely geared towards enlarging models to gauge, report and administer Intellectual Capital (Bontis, 2001;Guthrie, 2001;Brennan, 2001;Andriessen, 2004;Chen, Zhu & Xie, 2004;Striukova, Unerman & Guthrie, 2008;Dumay, 2009) in addition to assessing its role in organisations bottom line and worth (Chen, Cheng & Hwang, 2005;Tseng and Goo, 2005;Bharathi, 2008;Sharabat,i Jawad & Bontis, 2010). Third phase spanned the years 2011 to 2022 and was majorly oriented towards assessing the consequential effect of Intellectual Capital on performance (Joshi, Cahill, Sidhu & Kansal, 2013;Lu, Wang & Kweh, 2014;Xu and Wang, 2018;Asiaei, Jusoh & Bontis, 2018;Chatterjee, Chaudhuri, Thrassou & Sakka, 2021;Xu and Li, 2020;Campos, Dias, Teixeira & Correia, 2022;Prasojo, Yadiati, Fitrijanti & Sueb, 2022;Bataineh, Abbadi, Alabood & Alkurdi, 2022), competitive strength (Jardon & Martos, 2012;Yaseen, Dajani & Hasan, 2016;Jain et al, 2017;Niwash, Cek & Eyupoglu, 2022), innovative strength (Han & Li, 2015), knowledge governing practices (Kianto, Ritala, Spender & Vanhala, 2014), corporate governance (Hidalgo, García-Meca & Martínez, 2011;Soriya & Kumar, 2022) and sustainability (López-Gamero, Zaragoza Sáez, Claver Cortés & Molina Azorín ---, 2011; Massaro, Dumay, Garlatti & Dal Mas, 2018) on diverse sectors. Yet the study of IC so far has not been sufficient in analysing its ecological aspects and thus arose the need for the study of Green Intellectual Capital.…”
Section: Theoretical Backgroundmentioning
confidence: 99%